Eye-Tracking Provides a Sensitive Measure of Exploration Deficits After Acute Right MCA Stroke - Delazer, Margarete; Sojer, Martin; Ellmerer, Philipp; Boehme, Christian; Benke, Thomas (Frontiers in Neurology, 2018)
The eye-tracking study aimed at assessing spatial biases in visual exploration in patients after acute right MCA (middle cerebral artery) stroke. Patients affected by unilateral neglect show less functional recovery and experience severe difficulties in everyday life. Thus, accurate diagnosis is essential and specific treatment is required. Early assessment is of high importance as rehabilitative interventions are more effective when applied soon after stroke. Previous research has shown that deficits may be overlooked when classical paper-and-pencil tasks are used for diagnosis. Conversely, eye-tracking allows direct monitoring of visual exploration patterns. We hypothesized that the analysis of eye-tracking provides more sensitive measures for spatial exploration deficits after right middle cerebral artery stroke. Twenty-two patients with right MCA stroke (median 5 days after stroke) and 28 healthy controls were included. Lesions were confirmed by MRI/CCT. Groups performed comparably in the MMSE (patients and controls median 29) and in a screening of executive functions. Eleven patients scored at ceiling in neglect screening tasks, 11 showed minimal to severe signs of unilateral visual neglect. An overlap plot based on MRI and CCT imaging showed lesions in the temporo-parieto-frontal cortex, basal ganglia and adjacent white matter tracts. Visual exploration was evaluated in two eye-tracking tasks, one assessing free visual exploration of photographs, the other visual search using symbols and letters. An index of fixation asymmetries proved to be a sensitive measure of spatial exploration deficits. Both patient groups showed a marked exploration bias to the right when looking at complex photographs. A single case analysis confirmed that also most of those patients who showed no neglect in screening tasks performed outside the range of controls in free exploration. The analysis of patients’ scoring at ceiling in neglect screening tasks is of special interest, as possible deficits may be overlooked and thus remain untreated. Our findings are in line with other studies suggesting considerable limitations of laboratory screening procedures to fully appreciate the occurrence of neglect symptoms. Future investigations are needed to explore the predictive value of the eye-tracking index and its validity in everyday situations.